Comparison of Pap Smear Preparation Quality Containing Orange G and Without Orange G on the Results of the Papanicoulou Painting - Intan Prihatin; Budi Santosa; Fennisia Wibisono (Biomedika, 2020)
Examination procedure for pap smear preparation is influenced by fixation, drying and painting, and interpretation capability of examination. The Papanicolaou painting uses Harris Hematoxylin, Eosin Azure (EA) -50, and orange G. Orange G colors the orange matured and keratin cells Keratinizing-pink/orange cells. Chromatin in the nucleus will bind alkaline paint (hematoxylin) and cytoplasm protein will bind acidic paint (Orange G) and nucleus in the core will bind acid paint (EA 50) so that the cell will turn into pink with a blue core. The coloring stage according to procedure is using Orange G, but some PA laboratories do not use Orange G. The research goal is to know the comparison of pap smear preparation quality which contains orange G and without orange G towards papanicoulou painting result. The research type is experimental; the sample was 16 samples with two treatments namely coloring which using Orange G and without Orange G. The preparation quality which contains Orange G obtained moderate result of 12.5%, and good 87.5%. The preparation quality without Orange G was not good result of 6.3%, moderate 18.8%, and good 75%. The statistical test result of Chi Square and Kappa showed that the result was p>0.05 which means that comparison result of preparation quality which contains orange G and without orange G there was no significant difference.